Vertical Facial Skeletal Asymmetry and Occlusal Cant Relationship in Patients With Unilateral Cleft Lip and Palate. (August 2021) - Akarsu-Guven, Bengisu; Atik, Ezgi; Gorucu-Coskuner, Hande; Aksu, Muge
Objective: To evaluate the maxillary and mandibular vertical skeletal asymmetries, and the correlation between these asymmetries and occlusal cant in patients with unilateral cleft lip–palate (UCLP). Methods: Anteroposterior radiographs of 25 patients with UCLP (UCLP group, mean age: 20.98 ± 4.88 years) and 25 subjects without cleft (control group, mean age: 19 ± 2.86 years) were included. Independent samples t test, Mann-Whitney U test and Pearson correlation analysis were performed based on linear and angular measurements. Results: Lower facial horizontal asymmetry did not show statistically significant difference between the UCLP and control groups. However, vertical asymmetry of (a) the lateral cranial base ( P = .014), (b) the nasomaxillary region ( P < .001), (c) the maxillary dentoalveolus ( P = .001), and (d) the lower face ( P = .038) were all found to be significantly greater in UCLP group. The occlusal cant angle was also significantly greater in patients with UCLP compared to the controls ( P = .016). While the occlusal cant angle was found to be correlated with the vertical asymmetry of the occlusal cant ( r = 0.931, P < .001), maxillary cant angle was found to be correlated with the vertical asymmetry of the maxillary dentoalveolus ( r = 0.655, P < .001). Conclusions: There was no correlation between the occlusal cant and the vertical and horizontal skeletal asymmetries. Vertical asymmetries of the lower face and the medial cranial base were negatively correlated with the horizontal lower facial asymmetry.